Effects of black soya extract (Glycine soja) on histology femur of mice (Mus musculus) ovariectomized - mahriani, mahhriani; Yuniar, Resa Miftahatu; Hasanah, Masrurotul; Utami, Eva Tyas (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANA, 2021)
Bone is a dynamic structure and has the process to remodelling or regeneration. Bone remodelling includes the process of formation by osteoblasts and the process of resorption by osteoclasts. The balancing between formation and resorption are assisted by the estrogen hormone.Estrogen deficiency can lead the bone resorption. Ovariectomy is a model for estrogen deficiency by removing the ovaries. One way to overcome estrogen deficiency can be solved by offering phytoestrogens. This research have purpose to determine the effect of black soybean extract ( Glycine soja ) on the histology of the femur mice ( Mus musculus ) ovariectomized. In this research used a dose of black soybean extract as many as 0.42 g /ml/day and 0.63 g/ml/day, which are given orally for 30 days. The research is conducted with a completele randomized design with 4 treatments and 6 replications. Observations are made on the number of osteoblasts and the number of osteoclasts on the histological of the femur. The results showed that offering black soybean extract at a dose of 0.42 g/ml/day for 30 days have significantly increased the number of osteoblasts and have decreased the number of osteoclasts in the femur of ovariectomized mice.